International Students in the Era of Trump and Brexit: Implications, Constructions and Trends - Bartram, Brendan (Journal of International Students, 2018)
Across the Global North, many commentators have begun to note the expansion and spread of nationalist sentiments with some concern. Outside of the US, in the immediate aftermath of the U.K. vote to leave the European Union (EU) in the June 2016 referendum, there was an alarming increase in reported incidents of hate crime targeted at non-U.K. nationals (Burnett, 2017). These varied from physical attacks on individuals to verbal abuse and cyber assaults. Commentators suggested that the vote to leave had somehow—and for some people—legitimized the open display of negative attitudes toward foreigners and cultural difference, casual xenophobia, and indeed racist behavior (Khalili, 2016).